2021
DOI: 10.1007/s11426-021-1146-6
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in circularly polarized luminescence: molecular design, self-assembly, nanomaterials, and applications

Abstract: The research in circularly polarized luminescence has attracted wide interest in recent years. Efforts on one side are directed toward the development of chiral materials with both high luminescence efficiency and dissymmetry factors, and on the other side, are focused on the exploitations of these materials in optoelectronic applications. This review summarizes the recent frontiers (mostly within five years) in the research in circularly polarized luminescence, including the development of chiral emissive mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
180
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 388 publications
(182 citation statements)
references
References 376 publications
(510 reference statements)
1
180
0
1
Order By: Relevance
“…Chiral plasmonic nanomaterials could exhibit unprecedented enhanced CD, amplified dissymmetry factor (gfactor), engineerable and dynamic chiroptical responses 41 , thus holding a great opportunity in plasmon-based technological applications, such as chiral sensing 48,49 , chirality detection [50][51][52] , surface-enhanced spectroscopies 53,54 , and beyond 55,56 . By using novel chiral soft templates, nanoscale luminescent building blocks are able to self-organize into chiral luminescent nanomaterials exhibiting significantly enhanced circularly polarized luminescence 28,[57][58][59][60][61] . Thanks to their promising photophysical properties, chiral luminescent nanomaterials have attracted significant attention in diverse areas, such as biological science 62 , 3D display 63 , spintronics 64,65 , enantioselective photochemistry 36,66 and information encryption 67,68 .…”
Section: Introductionmentioning
confidence: 99%
“…Chiral plasmonic nanomaterials could exhibit unprecedented enhanced CD, amplified dissymmetry factor (gfactor), engineerable and dynamic chiroptical responses 41 , thus holding a great opportunity in plasmon-based technological applications, such as chiral sensing 48,49 , chirality detection [50][51][52] , surface-enhanced spectroscopies 53,54 , and beyond 55,56 . By using novel chiral soft templates, nanoscale luminescent building blocks are able to self-organize into chiral luminescent nanomaterials exhibiting significantly enhanced circularly polarized luminescence 28,[57][58][59][60][61] . Thanks to their promising photophysical properties, chiral luminescent nanomaterials have attracted significant attention in diverse areas, such as biological science 62 , 3D display 63 , spintronics 64,65 , enantioselective photochemistry 36,66 and information encryption 67,68 .…”
Section: Introductionmentioning
confidence: 99%
“…[18] The reports also included introducing of special functional groups through the intramolecular charge transfer (ICT) mechanism [19,20] and by modifying the geometrical configurations. [21,22] Liu et al have reported the a photocontrolled hierarchical chirality transfer and a switchable chiroptical helical self-assembly system derived from a photosensitive cinnamic acid derivative gelator. This type of cinnamic acid derivative can be transformed from the superhelical form to nanokebab under UV-irradiation, generating opposite helicity and chiral nanostructures that can further convey their chirality to achiral dyes and promote amplified CPL emission.…”
Section: Doi: 101002/adma202202309mentioning
confidence: 99%
“…[ 18 ] The reports also included introducing of special functional groups through the intramolecular charge transfer (ICT) mechanism [ 19,20 ] and by modifying the geometrical configurations. [ 21,22 ] Liu et al. have reported the a photocontrolled hierarchical chirality transfer and a switchable chiroptical helical self‐assembly system derived from a photosensitive cinnamic acid derivative gelator.…”
Section: Introductionmentioning
confidence: 99%
“…Chiroptical materials with circularly polarized luminescence (CPL) have become prominent due to their wide potential applications such as 3D displays, [ 1–7 ] photoelectric devices, [ 8 ] optical sensors, [ 9–11 ] chiroptical switches, [ 12–16 ] and encrypted storage of information. [ 17–18 ] Among them, chiroptical switches, especially CPL switches, have attracted considerable interest and will promote the next‐generation developments of smart materials based on reversible changes between two states after being exposed to various external stimuli, such as light irradiation, chemicals, pH changes, redox reactions, temperature, film tilting, mechanical forces, and so on.…”
Section: Introductionmentioning
confidence: 99%